Pemberdayaan UMK Mina Sejahtera (Sun Ti Sukaku) dalam inovasi Mi Badoghak dan Mi Bakso Ikan Kuah Rempah sebagai produk unggulan daerah yang bernilai Ekonomi - Dian Iriani; N. Ira Sari; Bustari Hasan; Elvrin Septyanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Mina Sejahtera's (Sun Ti Sukaku) Micro and Small Enterprises (MSE) is a business group that has a legal entity consisting of 10 members with products in the form of badoghak noodles and spicy sauce fishball noodles. Badoghak comes from the Kampar District language which means savory taste. The purpose of implementing this activity for the community is to train the Mina Sejahtera MSE group in creating new innovations in processing fishery products in the form of Badoghak Noodles and Spicy Sauce Fishball noodles as regional superior products that are economically viable. The benefits of this activity in addition to the formation of MSE groups that can make both badoghak noodles and spicy sauce fishball noodles products so that in the end they can increase the income of the MSEs group, they can also develop the potential of the area. From the results of this activity, it was found that training in new product development innovation in the Mina Sejahtera MSE group has been successfully implemented and has been introduced/promoted both at the local and national scale. Furthermore, this product has also been able to improve the community's economy, especially the Mina Sejahtera MSE group.